Use of Single Dose Ceftriaxone as Prophylactic Antibiotic during Caesarean section in Dhaka National Medical College Hospital - Khatun, Mst Hosna Ara; Arzu, Jahanara; Haider, Zulfe Ara (Journal of Dhaka National Medical College & Hospital, 2015)
Introduction : Caesarean section is a major operation, with great potential benefit, but also with substantial risks for both mother and baby. Inappropriate and prolonged use of antibiotics is a serious problem in caesarean section. Materials and Methods : This prospective study was done in the Departments of Obstetrics and Gynaecology in Dhaka National Medical College Hospital from 1st July, 2013 to 31st December, 2013. Women undergoing caesarean delivery, both emergency and elective were included. Ceftriaxone was used for antibiotic prophylaxis after separation of baby from mother and were follow up to see any feature of infection during hospitalization. Results : Present study showed that 36% women between 20 to 25 years of age and families came from urban (42%) and urban slum (31%) underwent caesarean section. Emergency caesarean section constituting 67% cases. The major indication for caesarean section was fetal distress (25%). Febrile morbidity after caesarean section was developed in 8% patients and among them 6% patients had underlying infectious morbidity. Superficial wound infection had occurred in 4% patients and only 2% developed urinary tract infection. Staphylococcus aureus (33.33%), escherichia coli (16.66%), klebsiella (16.66%) were found in wound infection and only escherichia coli (33.33%) was found in urine after caesarean section. Duration of hospital stay commonly was 4 to 5 days and only 4% cases hospital stay was more than 7 days. Conclusion : Single dose regimen with ceftriaxone as a prophylaxis during caesarean section is effective in preventing surgical infectious morbidities and also reduces duration of hospital stay. J. Dhaka National Med. Coll. Hos. 2015; 21 (01): 12-16